Religion, “sects” and social control in Xi Jinping’s China - INTROVIGNE, MASSIMO (2022)
Xi Jinping’s legal and administrative reforms in the field of religion have had a great impact in Chinese society. All three segments of the religion suffered the “red market”, which includes the five state-controlled religions; the “black market” of forbidden cults (or xiejiao); and the “gray market” of churches, temples and Mosques technically illegal, but sometimes tolerated. During the Xi administration, many steps were taken to eliminate the “gray market,” either by convincing congregations to join the official “red market,” or by destroying places of worship and arresting local leaders. Dissident Catholic congregations were also eliminated through a combination of police repression and diplomatic agreements with the Vatican. A paradigmatic case study is represented by the Life Zen Temple, a movement that went from the “red” to the “gray” and finally to the “black” market as an effect of Xi’s new attitude towards religion.